Inequality and U.S. Public Opinion on Foreign Aid. (September 2019) - Lee, Hak-Seon
I investigate how the level of inequality affects American public opinion on foreign aid. As the level of inequality increases across the United States, the majority of the public will be more likely to demand the government implement policies that should ameliorate severe inequality in society. Assuming that government resources are limited, a greater level of inequality in American society may weaken public support for foreign aid because the public may prioritize providing social safety nets and welfare programs in domestic milieu over granting foreign aid to developing countries. In addition, as inequality widens, the public may perceive economic globalization as one of the main causes of inequality; thus, their overall support for globalization will decline. As a result, American support for global engagement will be negatively affected, and public support for foreign aid may decrease. An empirical test using public opinion data in 50 U.S. states since the 1980s confirms my theory: widening inequality both across states and within a given state does weaken public support for U.S. foreign aid.